Comparison of Patient's Satisfaction with Pharmaceutical Care Services in Ownership-Based Pharmacies in Semarang, Indonesia - Nisa Febrinasari; Abdur Rosyid; Fadhila Huswatunnida (Borneo Journal of Pharmacy, 2022)
Implementation of pharmacists services provided in all pharmacies must meet the standard of pharmaceutical services guidelines, including the provision of drug information. The study aims to compare the patient's perception of drug counseling services by pharmacy staff based on the type of pharmacy ownership (franchise/non-franchise) in Semarang. This research is an observational study with a cross-sectional design. Samples were taken of 286 respondents with a quota sampling technique. Data were collected using an online google form questionnaire tested for validity and reliability. The statistical analysis results used the Mann-Whitney test with a p-value of <0.05. There is no significant difference between the patient's perception of the drug information counseling services by pharmacy staff at the franchise or non-franchise pharmacies in Semarang with a p-value of 0.264. This study also found that the standard information given by pharmacy staff is healthy eating and education about antibiotics used in the common cold. In addition, only 55% of respondents were sure that the pharmacy staff who gave them drug information in pharmacies was a pharmacist. Consequently, we humbly recommend that pharmacists consistently wear their pharmacist identification.